Comparison of the Variation of Coarse Aggregate Gradation on the Strength of Concrete - Laras, Dwivan Dhama; Pranowo, Dadang Dwi; Rodiyani, Megalita; Amin, M. Shofi'ul; Khomari, Mohamad Galuh (Universitas Negeri Padang, 2024)
Concrete as the main construction material has an important role in determining the strength and reliability of a construction project. The quality of concrete is influenced by the properties of its constituent materials, such as gravel, sand, cement and water. Testing the compressive strength of concrete is an important step to assess its quality and ensure it meets construction standards. Although previous research has compared the compressive strength of concrete and changes in aggregate volume, this research still covers limited dimensional variations and further exploration of aggregate dimensional variations is needed. This laboratory study used a conventional concrete design according to SNI 03-2834-2000, with compressive strength tests carried out at the Material Testing Laboratory, part of the Civil Engineering Department at Politeknik Negeri Banyuwangi Banyuwangi. The experimental results recorded in the fourth chapter show that at 7, 14, and 28 days, type AG 10 has the highest compressive resistance value, statistically significant mean value, and also shows that type AG 40 has the lowest compressive strength value. Therefore, it can be concluded that the smaller the size variation of coarse aggregate, the higher the compressive strength of concrete. These findings provide a comprehensive picture of the compressive strength characteristics of concrete with varying coarse aggregate sizes.